Association between the Functionality of Pelvic Floor Muscles and Sexual Satisfaction in Young Women - Caroline Darski; Lia Janaina Ferla Barbosa; Luciana Laureano Paiva; Adriane Vieira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Objective The objective of this study is to associate the results obtained while assessing the pelvic floor muscles (PFM) functionality with the score of sexual satisfaction of young adult women. Methods This is an observational and cross-sectional study. The inclusion criteria were women aged between 20 and 40 years who have had sexual intercourse, nulliparous, BMI lower than 25 kg/m2, and absence of pelvic floor dysfunction. The evaluation consisted of both the medical history and assessment of the PFM functionality using the Perina pressure biofeedback and Oxford Scale. We measured sexual satisfaction using the Female Sexual Quotient questionnaire and used the KolmogorovSmirnov test to verify the normality of the data. We analyzed non-parametric variables using the Spearman correlation test. The significance level was 5 %. Results A total of 80 women with a median age of 26 years and median BMI of 21.64 kg/m2 participated in this study. We divided the subjects into two groups, best and worse PFM functionality, according to median Perina pressure biofeedback and Oxford scale. We found no difference between the groups when comparing the sexual satisfaction scores. There was only a slight significant correlation between the Contraction Voluntary Average obtained using the pressure biofeedback and the primary domain (r = 0.27; p = 0.01). Conclusion This study found a slight correlation between PFM functionality and the functionality of the primary domain of the Female Sexual Quotient questionnaire. Therefore, it is not possible to state whether there is an association between the PFM functionality and female sexual satisfaction in young adults.